Xanthomonas resistance in Hungarian 4 spice pepper varieties - F. Márkus (International Journal of Horticultural Science, 2001)
With a view to further enhance the reputation of Hungarian spice pepper it was necessary to improve resistance to the bacterium Xanthomonas campestris pv.vesicatoria, the most dangerous pathogen of pepper varieties. From among the familiar resistance genes in Hungary only the gene Bs-2 could provide sufficient protection against the aggressiveness spectrum of the bacterium species X.c.pv. vesicatoria. The first results of the resistance breeding are the spice pepper varieties Kaldom and Kalorez. In addition to the Bs-2 gene attempts are also being made at building in a gds gene into pepper, a gene creating a general defense system, a different strategy towards Xanthomonas campestris pv. vesicatoria.